Evaluating the effects of road geometrical design towards spot speed distribution on arterial road - Mohd Maksid, Noor Hafiza; Kadar Hamsa, Abdul Azeez (Malaysian Institute of Planners, 2014)
Drivers travel at speeds they judge to be comfortably achievable in relation to the prevailing conditions and road geometrical design. The relationship between road geometrical design and speed of vehicles traveling in is very prominent. Speeds vary according to the perception of constraint imparted to the drivers by the road geometrical design. In a broader sense, these two factors are often interrelated with speed limits and road safety. The purpose of this study is to investigate how road geometrical design could influence the speed of vehicles on arterial road. Two roads with different geometric design were compared: arterial road with straight stretch and arterial road with curved stretch. The study was carried out by analyzing the speed characteristics between these two road stretches and it was discovered that vehicles traveling on straight road stretch tend to travel at higher speed than curved road stretch. The difference in the mean speed of the straight road and the curved road was tested for statistical significance by using t-test. The results show that there exists difference in the mean speed of the vehicles traveling at straight and curved road stretches. It was also found that the existing speed limit of the selected road stretches is lower than the 85th percentile speed. The 85th percentile speed is a commonly used measure to decide speed limit on a road. The vehicles were traveling at higher speed along straight stretch of road than curved road stretch. Few recommendations on strengthening the enforcement and improving speed reduction measures are drawn to discourage drivers driving at high speed to make roads free from accidents.